The Correlation of Students’ Grit to Their Achievement at STKIP Muhammadiyah of Southwest Aceh - Tajriani, Ainain; Adani, Sukri (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2025)
The grit theory, proposed by Duckworth et al. (2007 in Martin et al., 2022) emphasizes that persistence and passion for pursuing long-term goals are more crucial for achieving success than innate talent alone. In this study, Grade Point Average (GPA), a widely recognized indicator of student achievement, was selected as one of the key variables. The objective of this research was to assess the level of student grit and examine its relationship with academic performance at STKIP Muhammadiyah Aceh Barat Daya. A total of 136 students participated, comprising 75 English majors and 61 Mathematics majors. Participants were evaluated using the Duckworth Grit Scale, an 11-item assessment. Utilizing a quantitative correlational design, the study measured GPA and analyzed the data through Pearson correlation using SPSS. The findings revealed that the average level of grit among the 136 participants was moderate, with an average score of 40.10, translating to 40.1%. English majors scored an average grit level of 39.59 or 39.59 %, while Mathematics majors had an average grit level of 40.74 or 40.74 %. Moreover, the study established a significant correlation between Grit and Students’ Achievement (p < 0.001, r = 0.317). When analyzed separately, the correlation was weak among the 75 English students (p = 0.034, r = 0.245), while the 61 Mathematics students exhibited a moderate correlation (p < 0.001, r = 0.422). In conclusion, this study confirms that persistence is positively correlated with GPA, underscoring its importance in academic achievement.